Validasi Metode Analisis Tetrasiklin pada Ikan Nila (Oreochromis sp.) menggunakan Alat Kromatografi Cair Kinerja Tinggi (KCKT) - Nisa Hakimah; Gagak Donny Satria; Wari Pawestri; Soedarmanto Indarjulianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Antibiotics are substances that capable of inhibiting the growth of or killing microorganisms. The presence of residues in the tissues are associated with continuous use of antibiotics for long periods of time. The antibiotic residue that is often detected in freshwater fishery products is tetracycline. One method of analysis of tetracycline residues in fish meat is widely developed using high performance liquid chromatography (HPLC). This research was aimed to validate the method of analysis of tetracycline content in tilapia meat by using HPLC Shimadzu 6.1. The mobile phase consisting of methanol: acetonitrile: oxalic acid (5:15:80) with 1 ml / min flow rate, detector UV Vis with wavelength 355 nm, and C18Shim-pack column size 150 L x 4,6 mm at temperature of 30oC. The result of this research showed values corresponding to validation criteria based on parameters of specificity, precision, accuracy, linearity, limit of detection, and limit of quantification. Tetracycline analysis using HPLC tool has good and acurate validity as the first step in detecting the tetracycline level in tilapia meat.